4(2x+9)=-40+44

Simple and best practice solution for 4(2x+9)=-40+44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+9)=-40+44 equation:



4(2x+9)=-40+44
We move all terms to the left:
4(2x+9)-(-40+44)=0
We add all the numbers together, and all the variables
4(2x+9)-4=0
We multiply parentheses
8x+36-4=0
We add all the numbers together, and all the variables
8x+32=0
We move all terms containing x to the left, all other terms to the right
8x=-32
x=-32/8
x=-4

See similar equations:

| 3n+1=-6-4n | | 5x–45=–10 | | -4(v-75)=-48 | | 2(t−5)=48 | | 6x+3=5x–20 | | 40=5(d-72) | | X+6÷3=2x÷4 | | -36=-6(f-78) | | 9(m−3)+3m=7m+43 | | -7=3+2/3x | | -5=x-1/5 | | -5(4x-4)=4(5-5x)+0 | | -4.68=u/6+3 | | 6(1+3m)=-8(5-2m)-4 | | X2+3x+1=4x+3 | | 3a+7a=-5+4a-1 | | 5(x-57)+15=15 | | 2/3(c-1)=2c+1/2 | | 1.1+w/7=-16.4 | | 9.8=6.1+-d | | 8(2y+6)5y=37 | | -2(-4x–8)=-29–7x | | (x+7)+7=180 | | x+2x-12=12-5x | | 3(i-3)-(4i)=-13 | | -2(5x+4)=5(4-2x)-28 | | 4x+5+3x+13=180 | | -4x-15=46 | | 3r–3+2r=13–3r | | 4x-15=56 | | (y+5)^2=2y^2+11y+23 | | -a+7=-11+2a |

Equations solver categories